Penerapan model kooperatif tipe NHT untuk meningkatkan aktivitas dan hasil belajar matematika pada materi penjumlahan dan pengurangan bilangan Cacah kelas I MIN 10 Aceh Besar - Rakhimah, Rakhimah (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this study was to improve the activities and learning outcomes of Mathematics on the Summation and reduction of the number of students in grade I MIN 10 Aceh Besar. The learning model used in this study is the NHT cooperative type. The subjects of this study were students of class I MIN 10 Aceh Besar. The number of students is 23 students with 11 male students and 12 female students. This research was conducted in the 2019/2020 school year within a period of 3 months, from September 2019 to November 2019 in the odd semester. The methodology of this research is Classroom Action Re-search (CAR) consists of two cycles and each cycle consists of two meetings. In each cycle consists of planning, implementation, observation and reflection. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Observation data is done by looking at the activeness of students in the learning process. Data were ana-lyzed by means of percentage statistics. The results showed that an increase in student learning activities in both cycles, from the category of being good enough and the good category increasing to very good. Completeness of student learning outcomes has increased from 43.48% in the pre cycle increased to 65.22% in the first cycle and increased to 82.61% in the second cycle. The use of the NHT Cooperative Model can increase the activities and learning outcomes of Mathematics in the Summing and subtraction count numbers of students in class I MIN 10 Aceh Besar in the Academic Year 2019/2020.